(untitled) (Advances in Applied Biological Research, 2025)
Background: Type 2 diabetes mellitus is associated with various complications, including potential impacts on bone health. Although elderly patients with Type 2 diabetes mellitus may exhibit normal bone mineral density they are paradoxically at a higher risk for fractures. The underlying mechanisms remain multifactorial, involving glycaemic control, hormonal regulation, and nutrient deficiencies. Objective: To evaluate bone mineral density in elderly patients with Type 2 diabetes mellitus and investigate its relationship with glycaemic control, vitamin D levels, and calcium status.Patients and Methods: A prospective, cross-sectional study was conducted on 46 patients above 65 years of age in Merjan teaching hospital babil, Iraq, from May 2024 to May 2025. Data collected included demographics, HbA1c levels, serum vitamin D and calcium, and bone mineral density measured via DEXA scans at the spine and hips. Results: Osteoporosis was present in 54.3% of patients, with 34.8% of patients were classified as osteopenic. The majority of patients were females. A positive correlation was found between HbA1c and DEXA scan T-scores (r = 0.313, p = 0.034), patients with poor glycaemic control (mean HbA1c = 9.2%) had a higher prevalence of osteoporosis. No significant correlations were found between bone mineral density (Dexa T-scores) and serum vitamin D (r = -0.057, p = 0.705) or calcium levels (r = -0.080, p = 0.597). The right hip showed the highest site-specific prevalence of osteoporosis (41.3%).Conclusions: Osteoporosis is highly prevalent among elderly patients, particularly women. Poor glycemic control (high HbA1c) and increasing age are significantly associated with lower bone density. Recommendation: DEXA scans of multiple sites, especially the spine and hips, are essential for detecting osteoporosis in this population.